Optimalisasi Desain Reaktor Fotokatalitik untuk Degradasi Formaldehida Menggunakan Substrat Stainless Steel Mesh - Dewi, Renita; Adhi, Pribadi Mumpuni; Nufus, Tatun Hayatun; Kamal, Dianta Mustofa (Jurnal Teknik Terapan, 2025)
Indoor air quality (IAQ) plays a crucial role in the health and comfort of building occupants, where pollutants like formaldehyde can cause serious health issues. To reduce formaldehyde levels, photocatalytic oxidation (PCO) technology using titanium dioxide (TiO2) substrates has been shown to be effective. This study aims to optimize the PCO system design using TiO2-coated stainless steel mesh substrates in a honeycomb monolith reactor configuration to enhance formaldehyde degradation efficiency. Three variations of stainless steel mesh layers (5, 10, and 15 layers) were tested to evaluate their impact on formaldehyde (HCHO) concentration reduction. The results indicated that increasing the number of mesh layers significantly improved the formaldehyde degradation efficiency. The highest efficiency, 96.06%, was observed with 15 layers, compared to 74.67% with 5 layers and 83.19% with 10 layers. The increase in mesh layers enlarged the surface area of the substrate, enhancing the reaction area and interaction between pollutants and the photocatalyst. This study suggests using more than 10 layers of stainless steel mesh in the PCO system design to achieve optimal performance in formaldehyde pollutant reduction. The findings are expected to contribute significantly to improving indoor air quality, particularly in areas exposed to pollutants such as cigarette smoke.